ANALISIS AFIKSASI DALAM NOVEL DIRAWU KELONG KARYA AHMAD BAKRI - Rahayu; Ratnawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study investigates the forms, functions, and meanings of affixation (kecap rundayan) in the Sundanese-language novel Dirawu Kélong by Ahmad Bakri. Using a descriptive qualitative method and content analysis approach based on Sudaryat’s (2013) morphological theory, 420 affixation instances were identified and classified into five types: prefixation, infixation, suffixation, confixation, and ambifixation. The results show suffixation as the most dominant form (54.76%), followed by prefixation (24.05%), ambifixation (12.86%), infixation (5.48%), and confixation (2.86%). In terms of function, affixed words were mostly nouns (44.52%), verbs (41.90%), and adjectives (7.86%). Each affix form contributes specific grammatical meanings, such as indicating possession, passive/active voice, or plurality. The research highlights the richness of Sundanese morphology within literary texts and emphasizes its importance for preserving regional language through literature. It also serves as a linguistic reference for both academic and educational contexts, supporting Sundanese language maintenance and revitalization among younger generations. Keywords: Keywords: affixation; Sundanese morphology; linguistic analysis; novel; regional language preservation